1999
DOI: 10.1108/08876049910282682
|View full text |Cite
|
Sign up to set email alerts
|

International services advertising: an examination of variation in appeal use for experiential and utilitarian services

Abstract: Examines differences in emotional and rational advertising appeal use across experiential and utilitarian services for 11 culturally diverse countries. Pooled across countries, rational appeals were found to be more dominant in utilitarian service advertising, while emotional appeals were used more heavily in experiential service advertising. On a country by country basis, utilitarian service advertisements consistently used a larger number of rational appeals, and experiential service advertisements contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 42 publications
0
69
0
4
Order By: Relevance
“…For example, Albers-Miller and Stafford (1999a) found that Taiwan services ads contained significantly more emotional appeals as compared with ads for goods. Conversely, U.S. advertisers used significantly more emotional appeals for goods as compared with services.…”
Section: Message Appealsmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, Albers-Miller and Stafford (1999a) found that Taiwan services ads contained significantly more emotional appeals as compared with ads for goods. Conversely, U.S. advertisers used significantly more emotional appeals for goods as compared with services.…”
Section: Message Appealsmentioning
confidence: 97%
“…Moreover, many topics related to international advertising need more attention than they have received. In particular, international advertising research has often ignored services (Albers-Miller and Stafford 1999b;Kanso and Kitchen 2004), despite the fact that services are the fastest-growing segment of the global market (Javalgi and White 2002).…”
Section: Advertising Regulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rational advertising assumes that consumers make rational decisions. Rational advertising's goal is thereby to change consumers' beliefs about a brand using arguments or reason (Albers-Miller & Stafford, 1999). Rational appeals present facts straightforwardly and objectively (Stafford & Day, 1995).…”
Section: Emotional and Rational Appeals In Csr Communicationmentioning
confidence: 99%
“…In contrast, emotional appeals target the emotional or experiential facet of consumption. Such appeals seek to make the consumer feel good about the product, by creating a likeable or friendly brand (Albers-Miller & Stafford, 1999).…”
Section: Emotional and Rational Appeals In Csr Communicationmentioning
confidence: 99%